EFEKTIVITAS KERJASAMA ANTARA UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DENGAN KEMENTERIAN HUKUM DAN HAM REPUBLIK INDONESIA DALAM MENANGANI PENCARI SUAKA (Studi Kasus: Penanganan Pencari Suaka dan Pengungsi di Pekanbaru) - Sinaga, Alifia Ayu Kinanti Yusin; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This world's openness not only has a positive effect but also a negative, one of which is the arrival of many immigrants, refugees or assylum seekers. This research has a formula for the effectiveness of cooperation between the government and international organizations to handle these refugees who came to Indonesia teritory.            This study used observation method, interview and library research. As for the sources of data used are primary and secondary data, also the quantity of refugees and the facilities they got from Immigration Detention House and UNHCR Pekanbaru. In addition to using a descriptive qualitative research method with the pluralism perspective, the theory of effectiveness, the theory of international organization and human security concept.            Based on the data analysis carried out with effectiveness indicators, it came about that the cooperation between Ministry of Law and Human Rights of Riau Province through Immigration Detention House with UNHCR in dealing with refugees residing temporarily in Pekanbaru is effective depend on all of the facilities they got, like education, monthly living cost, etc. Keywords : UNHCR, government, refugees, effectiveness, cooperation